2010
DOI: 10.1159/000315063
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal Crohn’s Disease Mimicking Autoimmune Inner Ear Disease: A Histopathological Approach

Abstract: Patients with autoimmune inner ear disease develop rapidly progressive sensorineural hearing loss over a period of several weeks or months, often accompanied by vestibular loss. This disease can occur as a distinct clinical entity or in association with an underlying autoimmune disorder. Treatment comprises immunosuppression by corticosteroids, cytostatic drugs or tumor necrosis factor-α antagonists. We report histopathological and immunohistochemical findings of the inner ear of a patient with a granulomatous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…For example, researchers have reported that patients with Meniere's disease demonstrate substantial recovery from symptoms such as fluctuating SNHL, vertigo, and roaring tinnitus after receiving systemic corticosteroid treatment, and the evidence points to an underlying immune-mediated component to this disease ( Hughes et al , 1983 ; Derebery et al , 1991 ). Some multisystem autoimmune diseases including Wegener's granulomatosis, Cogan syndrome, Lupus ( McCabe, 1989 ; Moscicki et al , 1994 ), and even Crohn's disease ( Dettmer et al , 2011 ) have been implicated in cochlear pathogeneses. Though speculative, the strong immune activity associated with these multisystem autoimmune diseases may be responsible for some degree of cochlear tissue degeneration leading to SNHL secondary to the systemic autoimmune disorder.…”
Section: Immune-mediated Pathogenesis In the Inner Ear: Potential Trementioning
confidence: 99%
“…For example, researchers have reported that patients with Meniere's disease demonstrate substantial recovery from symptoms such as fluctuating SNHL, vertigo, and roaring tinnitus after receiving systemic corticosteroid treatment, and the evidence points to an underlying immune-mediated component to this disease ( Hughes et al , 1983 ; Derebery et al , 1991 ). Some multisystem autoimmune diseases including Wegener's granulomatosis, Cogan syndrome, Lupus ( McCabe, 1989 ; Moscicki et al , 1994 ), and even Crohn's disease ( Dettmer et al , 2011 ) have been implicated in cochlear pathogeneses. Though speculative, the strong immune activity associated with these multisystem autoimmune diseases may be responsible for some degree of cochlear tissue degeneration leading to SNHL secondary to the systemic autoimmune disorder.…”
Section: Immune-mediated Pathogenesis In the Inner Ear: Potential Trementioning
confidence: 99%
“…Previous studies have revealed that 46–57% of adult patients with IBD present with sensorineural hearing loss as an extraintestinal manifestation ( 85 , 86 ); however, few reports have mentioned the roles of monocytes/Mφs. Dettmer et al reported that the temporal bones of patients with IBD exhibited mild chronic inflammation, poorly defined granulomas, and CD68-positive Mφ infiltration ( 87 ). IBD may also be associated with Cogan's syndrome, a rare disorder characterized by eye and inner ear inflammation manifesting as interstitial keratitis and audiovestibular dysfunction, respectively ( 88 ).…”
Section: The Role Of Inner Ear Macrophages In Aiedmentioning
confidence: 99%
“…Autoimmune disorders affecting the brain, eyes and ears are summarized as “brain-eye-ear syndromes” (BEE) ( Table 7 ) 290 . Medical history is completed by questions about symptoms of the gastrointestinal tract (e. g., Crohnʼs disease, ulcerative colitis, celiac disease) 291 292 293 , the locomotor system (e. g., rheumatoid arthritis), the kidneys (e. g., ANCA-positive vasculitis), and the thyroid gland (e. g., autoimmune thyroiditis) 285 .…”
Section: Episodic Vestibular Syndromesmentioning
confidence: 99%
“…Die Systemanamnese wird abgerundet durch Fragen nach Symptomen im Bereich des Gastrointestinaltraktes (z. B. bei M. Crohn, Colitis ulcerosa, Zöliakie) 291 292 293 , des Bewegungsapparates (z. B. rheumatoide Arthritis), der Niere (ANCA-positive Vaskulitiden) und der Schilddrüse (Autoimmunthyreoiditis) 285 .…”
Section: 432 Diagnostisches Procedereunclassified